Технологические особенности использования автомобильного и электрического транспорта в логистических системах города - Алпеева, Анна Викторовна (Eastern-European Journal of Enterprise Technologies, 2014)
The aspects of the electric transport operation to provide the logistic system maintenance are under consideration. The road congestion elements have been classified taking into account the cargo tram operation in transport maintenance of the logistic system elements/ The term of city logistic centre has been offered to denote the centre to organize the logistic system operation.